DIMENSI PENDIDIKAN KARAKTER ANAK USIA DINI MENURUT IBNU QAYYIM AL-JAUZIYYAH - Zaimuddin (Program Studi Pendidikan Islam Anak Usia Dini, 2021)
Character education is one of the roles of educational institutions to foster the nation's young generation so that they behave properly and correctly in accordance with the norms prevailing in society. To produce young people with the characteristics as they aspire together, the role of education for early childhood is very important as a foundation for self-formation. Most educators both teachers and parents are less aware of the fundamental reasons for early character education which is also referred to as the golden age. Ibn Qayyim provides a solution to the dimensions of early character education so that in the future children will be good in their behavior and manners and so forth.